Remodelling Business UMK “Bakso Sip”: Ten Types of Innovation - Hidhayah, Anysha Nur; Rahmi, Vembri Aulia; Kurniawan, Aries; Ismanto, Hadi (Economic Education and Entrepreneurship Journal, 2023)
This research aims to find out how the implementation of "Bakso SIP" innovation with the Business Model Canvas and Ten Types Innovation methods. The research used a qualitative-descriptive method on "Bakso SIP" located in the Village, Pekauman, South Banjarmasin District, Banjarmasin City, South Kalimantan Province. The results showed that the owner of "Bakso SIP" has made three innovations in ten types of innovation, namely process innovation, channel innovation, and customer engagement, so that the business model of "Bakso SIP" has changed (remodeling) the business model canvas on the element of customer segments which used to only reach residents of the Pekauman area, Banjarmasin then more widely reach residents of Banjarmasin City. Customer relationships that used to be only with direct transactions can then make reservations in advance via WhatsApp Business and promote via Instagram, value proposition there is a change in service online reservation in advance. Key partnes join the online application.Keywords: Business Model Canvas, Inovation Business, Ten Types innovationDOI: http://dx.doi.org/10.23960/E3J/v6i2.153-161